Tantangan Islam Moderat di Era Disruption - Winarto Eka Wahyudi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
In addition to being a religion that occupies a majority position amid the diversity of religions in Indonesia, Islam in this archipelago country, is known as a religion that upholds the values ​​of tolerance and noble. The harmonious compounds between the substantial teachings of Islamic religion and the culture of the archipelago make this religion a distinct position in the hearts of the people. Unfortunately, this reality applies in pre-reform era to the back. After the collapse of the New Order era of 1998 ago to date, the face of Islam in Indonesia tends to be displayed with increasingly fierce and furious. This fact, aggravated by the increasingly sophisticated information technology, so participate in shaping opinion in the community, especially among followers of Islam. Thus, it is not difficult to find fellow Muslims clashing and facing each other due to differences in the acceptance of information from online media. Now, the phenomenon of blasphemy and cursing as if the daily menu of Indonesian Muslims, almost no day without the verbal abuse among Muslims. This is of course if left unchecked, will have an impact on the lunturnya spirit of moderation that has been the advantage of the nature of Islam in the archipelago. So, it becomes very relevant if the spirit of moderation (wasatiyah) re-echoed in the middle of millennial generations that most of his life drained away in the digital world.